1990
DOI: 10.1002/hep.1840110420
|View full text |Cite
|
Sign up to set email alerts
|

Single, Total Paracentesis for Tense Ascites: Sequential Hemodynamic Changes and Right Atrial Size

Abstract: Hemodynamic changes induced by a single, total paracentesis were evaluated in 21 patients with tense ascites from whom 4 to 16 L of ascites were drained over 2 to 8 hr with no serious complications. At 60 min, compared to baseline, there was an increase in cardiac output (7.7 +/- 0.5 to 8.5 +/- 0.6 L/min, p less than 0.02) and a tendency for right atrial pressure to decrease (9.3 +/- 0.8 to 7.50 +/- 0.8 mm Hg, NS), with no change in pulmonary capillary wedge pressure (10.9 +/- 0.9 to 10.7 +/- 0.9 mm Hg). Betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 26 publications
0
32
0
2
Order By: Relevance
“…30 The issue of whether paracentesis should be repeated daily with 5-liter paracentesis or a single total paracentesis has been resolved. 31,32 Titò et al 31 showed that total paracentesis was as effective and as safe as repeated partial paracentesis. Paracentesis causes an acute increase of cardiac output and a lowering of systemic vascular resistance, leading to a modest reduction of blood pressure.…”
Section: Paracentesismentioning
confidence: 99%
See 2 more Smart Citations
“…30 The issue of whether paracentesis should be repeated daily with 5-liter paracentesis or a single total paracentesis has been resolved. 31,32 Titò et al 31 showed that total paracentesis was as effective and as safe as repeated partial paracentesis. Paracentesis causes an acute increase of cardiac output and a lowering of systemic vascular resistance, leading to a modest reduction of blood pressure.…”
Section: Paracentesismentioning
confidence: 99%
“…Paracentesis causes an acute increase of cardiac output and a lowering of systemic vascular resistance, leading to a modest reduction of blood pressure. 32 Pulmonary capillary wedge pressure decreases at ϳ6 hours postparacentesis, whereas the right atrial pressure falls acutely following the onset of paracentesis, secondary to a reduction of intrathoracic pressure. 32 Since postparacentesis effective hypovolemia (PPH) can occur hours or days after the procedure (see below), volume expansion should commence once the paracentesis has been completed.…”
Section: Paracentesismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is not possible to obtain the abdominal pressure produce hemodynamic modifications. 11,12 A mechanical increase of abdominal pressure produced an esophageal luminal pressure with this method, and pressures obtained cannot be recorded. Direct puncture of varices at increase in wedge and free hepatic venous pressures without changes in hepatic venous pressure gradient with a concomi-endoscopy with 22-24 and without saline 20,25-28 perfusion appears to be the most reliable and sensitive technique for detant decrease in hepatic blood flow and an increase in variceal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 These changes in blood flows determine a decrease in the renin-angiotensin-aldosterone system and in the output of the sympathetic nervous system. 9,12,15 As a result, these changes in intra-abdominal pressure and vasoactive hormones could cause a reduction of intrahepatic vascular resistance and portal pressure, 17 with a concomitant decrease in variceal blood flow. 9 In our study, a reduction of variceal pressure of 30% was noted, which is similar to the 28% decrease in azygos blood flow previously observed.…”
Section: Discussionmentioning
confidence: 99%